Transcriptional Activity of Human Endogenous Retroviruses in Response to Prenatal Exposure of Maternal Cigarette Smoking - Bergallo, Massimiliano; Galliano, Ilaria; Daprà, Valentina; Pirra, Alice; Montanari, Paola; Pavan, Marzia; Calvi, Cristina; Bertino, Enrico; Coscia, Alessandra; Tovo, Pier-Angelo (American Journal of Perinatology, 2019)
Objective Transcription of human endogenous retrovirus (HERV) elements is usually suppressed by epigenetic factors such as DNA methylation and heterochromatin silencing by histone modifications. There is an association between maternal smoking during pregnancy and DNA methylation levels in placental tissue and in DNA from cord blood.Study Design We assessed the transcriptional activity of HERV-H, HERV-K, and HERV-W in umbilical cord blood from 47 term babies unexposed to tobacco smoke in utero and 23 term babies exposed to tobacco smoke in utero.Results In our population, the HERV-H, HERV-K, and HERV-W families were always transcriptionally active, and the levels of all HERVs (H, K, W) were significantly higher in unexposed than smoke-exposed babies.Conclusion This study provides preliminary information about the transcriptional activity of HERV-H, HERV-K, and HERV-W families in human umbilical cord blood.
Keywords: HERV-K; HERV-H; HERV-W; cigarette smoke